Public policy selectivity in solid waste in the covid-19 pandemic: exponentiating the vulnerability of the waste pickers’ cooperatives in Londrina- PR - Santos, Felipe Nepomuceno Coimbra; Borinelli, Benilson; Flor, Caroline Nayara Marilac; Aligleri, Lilian (Revista de Administração da UFSM, 2021)
Purpose: This article aimed to understand how the actions of the local state, given the pandemic scenario, produce structural selectivity in the sector of Waste Cooperatives in the face of coping with COVID-19 in the municipality of Londrina, State of Paraná. Design/methodology/approach: The study stands out as exploratory-descriptive and qualitative, using primary and secondary data extracted mainly from questionnaires registered with representatives of recycling cooperatives and official documents. We conducted structured interviews with leaders/representatives of 6 of the 7 cooperatives that have a service contract with the City of Londrina, between May 28 and June 9, 2020. Findings: Data analysis showed combined mechanisms of state selectivity (structure, ideology, processes, and coercion) that favor some actors and hinder access to others. The selectivity promoted by the State during the pandemic aggravated the crisis that was already developing locally in the sector. Although cooperatives have been affected in different ways, selectivity contributes in general to the greater dismantling of the sector and may even imply the unfeasibility of some of these social organizations. Originality/value: The study made it possible to analyze the existence of the concept of selectivity of the State, from a set of interests and actors involved in the state apparatus at a time of major health crisis. The study aims to contribute to the debate of public policies and actions to confront the COVID-19 in a sector considered essential to the well-being of society, by exposing the sectoral needs and actions or inactions of the federal government in structural selectivity.